PENDAMPINGAN PEMBENTUKAN KARAKTER DISIPLIN DAN TANGGUNG JAWAB MELALUI LATIHAN KEPANDUAN PENGHELA HIZBUL WATHAN PADA SISWA SMK MUHAMMADIYAH 2 LEKOK: Pendekatan Berbasis Aset Dalam Penguatan Karakter Disiplin Dan Tanggung Jawab Siswa SMK Muhammadiyah - Hamdan Robbani; Solchan Ghozali (Sekolah Tinggi Agama Islam Al-Muntahy, 2025)
This activity focuses on strengthening students’ discipline and responsibility through the implementation of the Asset-Based Community Development (ABCD) approach in Hizbul Wathan scouting activities at Muhammadiyah Vocational High School 2 Lekok, Pasuruan Regency. The main objective is to foster students’ awareness of discipline and responsibility as Islamic character values integrated into daily behavior. The program was conducted over four weeks, involving 30 members of the Penghela Hizbul Wathan scout group. The ABCD approach was applied by positioning students as active subjects in exploring and developing their personal and environmental potentials as assets for behavioral transformation, through the stages of Discovery, Dream, Design, Define, and Destiny. Data were collected through participatory observation, structured interviews, and self-reflection questionnaires, and analyzed using descriptive and thematic methods. The results revealed an average improvement of 44% in students’ character scores, particularly in punctuality, rule compliance, and group responsibility. Qualitative findings also indicated significant behavioral changes, reflective awareness of Islamic values, and enhanced cooperation among participants. The implications of this activity show that the asset-based approach effectively promotes participatory, contextual, and sustainable character development while reinforcing moral and spiritual values within Islamic education settings. This program serves as an adaptable model for character education initiatives in Islamic-based vocational institutions.